Contribution à l'étude de la qualité des eaux d'irrigation des nappes souterraines : phréatique et C.T dans le périmètre agricole de DEBILA - شوية, يحي; رواحنة, زين الدين (university of Eloued جامعة الوادي, 2019)
work, we examined a comparative study of the quality of irrigation water in the two layers of the free layer and the final compound of the zone. The results show that the water of the two layers is characterised by high hardness due to the high mineral concentration of magnesium and calcium. This is mostly due to the geological origin. From S.A.R's point of view, there is no restriction on the use of free-layer water, and for the final composite water, it is mild to moderate requiring special attention to sensitive crops. تعتبر المياه واحدة من اهم العناصر للحياة البشرية والتي لا يمكن باي شكل من الاشكال الاستغناء عنها لأساسيتها في جميع الاستعمالات اليومية للشرب الزراعة والصناعة. تناولنا في هذا العمل دراسة مقارنة لجودة مياه السقي في الطبقتين المائيتين الطبقة الحرة والمركب النهائي لمنطقة الدبيلة وتظهر النتائج ان مياه الطبقتين تتميز بقساوة عالية نتيجة ارتفاع التركيز المعدني للمغنيزيوم والكالسيوم وهذا راجع في الغالب الى الاصل الجيولوجي، من وجهة نظر S.A.R لا يوجد أي قيود على استخدام مياه الطبقة الحرة، وبالنسبة لمياه المركب النهائي فهي خفيفة إلى معتدلة تتطلب اً اهتمام خاص بالمحاصيل الحساسة.
مذكرة ماستر تخصص في منشئات الري
Keywords: groundwater, terminal complex, hardness, S.A.R, Mineral concentration, Calcium, Magnesium.; الطبقة الحرة، المركب النهائي، القساوة، S.A.R، التركيز المعدني، الكلسيوم، المغنزيوم.